(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
Recently, international refugee law has undergone important gender-sensitive developments that have made it possible to overcome the only apparent neutrality of the 1951 International Convention on the Status of Refugees. Nonetheless, States maintain a standoffish position that does not guarantee certainty in protecting women’s rights. This situation is linked to the fact that international refugee law was created to respond to the needs of a particular context, that of displaced persons of the Second World War. Its original version did not include a gender or sex perspective. In this paper, taking as a starting point the situation of Afghan women after the return of the Taliban to power last August, we will first analyze the gender-sensitive developments in international refugee law. First of all, the possibility of interpreting the elements necessary for granting refugee status in light of the gender perspective will be emphasized. Furthermore, the gaps that still exist, especially regarding the possibility of considering the so-called domestic or private violence as a form of gender-based violence justifying the granting of international protection under the 1951 Convention will be considered. In addition, the paper will propose a test that judges or competent authorities in each country should apply to consider whether the granting of international protection to women victims of gender-based violence would be justified. This test will be constructed in the light of the criteria developed by national and international case law, regarding gender-based violence.